2005
DOI: 10.1007/s10802-005-1831-1
|View full text |Cite
|
Sign up to set email alerts
|

A Multitrait?Multisource Confirmatory Factor Analytic Approach to the Construct Validity of ADHD and ODD Rating Scales with Malaysian Children

Abstract: Confirmatory factor analysis (CFA) was used to model a multitrait by multisource matrix to determine the convergent and discriminant validity of measures of attention-deficit hyperactivity disorder (ADHD)-inattention (IN), ADHD-hyperactivity/impulsivity (HI), and oppositional defiant disorder (ODD) in 917 Malaysian elementary school children. The three trait factors were ADHD-IN, ADHDHI, and ODD. The two source factors were parents and teachers. Similar to earlier studies with Australian and Brazilian children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 29 publications
6
62
0
1
Order By: Relevance
“…In particular, CFAs of the DSM-IV symptoms of ADHD, ODD, and CD consistently have found that the DSM-IV model fits better than alternative models (Beiser et al 2000;Burns et al 1997Burns et al , 2001DuPaul et al 1998;Gomez et al 2005;Muris and Meesters 2003). For example, across studies, the DSM-IV model that distinguishes two dimensions of ADHD symptoms fit better than a model specifying a single dimension of ADHD symptoms, similar to the model specified in DSM-III-R and in the Child Behavior Checklist (CBCL; Achenbach 1978Achenbach , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CFAs of the DSM-IV symptoms of ADHD, ODD, and CD consistently have found that the DSM-IV model fits better than alternative models (Beiser et al 2000;Burns et al 1997Burns et al , 2001DuPaul et al 1998;Gomez et al 2005;Muris and Meesters 2003). For example, across studies, the DSM-IV model that distinguishes two dimensions of ADHD symptoms fit better than a model specifying a single dimension of ADHD symptoms, similar to the model specified in DSM-III-R and in the Child Behavior Checklist (CBCL; Achenbach 1978Achenbach , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…There are several concerns about the heavy reliance on behaviour checklists for ADHD diagnosis. The discriminant validity of behaviour ratings for ADHD symptoms is far from impressive (Gomez et al, 2003(Gomez et al, , 2005. Levels of agreement between behavioural ratings across settings are low (Antrop et al, 2002;Gomez et al, 2003Gomez et al, , 2005Mares et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The discriminant validity of behaviour ratings for ADHD symptoms is far from impressive (Gomez et al, 2003(Gomez et al, , 2005. Levels of agreement between behavioural ratings across settings are low (Antrop et al, 2002;Gomez et al, 2003Gomez et al, , 2005Mares et al, 2007). Additionally, ratings are subject to the negative halo effect, which describes how one negative attribute or behaviour in a person can influence a rater to evaluate other behaviours and attributes negatively (Schachar, Sandberg, & Rutter, 1986;Stevens, Quittner, & Abikoff, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2003; Gomez et al 2003Gomez et al , 2005. These studies involved four different samples of children, rated on three different ADHD rating scales, from three different countries (Australia, Brazil, and Malaysia).…”
mentioning
confidence: 99%